Lactic acid bacteria : biodiversity and taxonomy - Holzapfel, W. H., 1942-; Wood, Brian J. B. (Wiley Blackwell, 2014)
"This book provides a much-needed and comprehensive account of the current knowledge of the lactic acid bacteria, covering the taxonomy, biochemistry, physiology and molecular biology of these scientifically and commercially important micro-organisms"--Resumé vydavatele
Keywords: bakterie mléčného kvašení; systematická mikrobiologie; fyziologie mikroorganismů; biodiverzita; lactic acid bacteria; systematic microbiology; microbial physiology; biodiversity; kolektivní monografie; collective monographs